"Sufferance fait ease en temps": word as image at St Michael-le-Belfrey, York. Issue 2 (2nd April 2016) - Reilly, Lisa; Shepard, Mary B.
Abstract: Nestled in the northeast corner chapel (window nII) of the parish church of St Michael-le-Belfrey, York, is a puzzling tracery light containing a roundel with a silver-stained disk inscribed with a corkscrew banderole in the center. The inscription, in Anglo-French, reads "Sufferance fait ease en tempe"—which can be best translated as "In time, from suffering comes ease." This article, the first to consider the roundel, identifies it as a fifteenth-century work—which places it a century earlier than the building in which it resides. Not original to its current location (or to the sunrays that now surround it), the roundel is discussed in terms of its design and possible provenance, as well as its relationship to devotional practices in England in the fifteenth century and its conspicuous use of Anglo-French.